2022
DOI: 10.1038/s41591-022-01916-x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor immune contexture is a determinant of anti-CD19 CAR T cell efficacy in large B cell lymphoma

Abstract: Axicabtagene ciloleucel (axi-cel) is an anti-CD19 chimeric antigen receptor (CAR) T cell therapy approved for relapsed/refractory large B cell lymphoma (LBCL) and has treatment with similar efficacy across conventional LBCL subtypes. Toward patient stratification, we assessed whether tumor immune contexture influenced clinical outcomes after axi-cel. We evaluated the tumor microenvironment (TME) of 135 pre-treatment and post-treatment tumor biopsies taken from 51 patients in the ZUMA-1 phase 2 trial. We uncove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 72 publications
2
83
0
Order By: Relevance
“…In addition, CXCL-9 levels were found to be highly correlated with CD45 + EVs and IL-10 plasma levels, as well as senescent CD8 + T cells. Notably, it has been reported that CXCL-9 expression in the tumor microenvironment at the pre-treatment stage affects the local immune landscape in patients treated with CAR-T cell therapy ( 17 ). Speculatively, CXCL-9 circulating levels may provide information about the role of the tumor microenvironment in the onset of ICANS ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CXCL-9 levels were found to be highly correlated with CD45 + EVs and IL-10 plasma levels, as well as senescent CD8 + T cells. Notably, it has been reported that CXCL-9 expression in the tumor microenvironment at the pre-treatment stage affects the local immune landscape in patients treated with CAR-T cell therapy ( 17 ). Speculatively, CXCL-9 circulating levels may provide information about the role of the tumor microenvironment in the onset of ICANS ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, CAR-T cell-induced neurotoxicity can be largely influenced by the pre-treatment tumor immune microenvironment, and by the crosstalk among lymphoma cells, myeloid cells, cytotoxic and regulatory T cells ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Semin Oncol 2017). Included in this perspective is an emerging concept of the immunoscore, which attempts to predict favorable responses based on infiltrating T-cell density ( 24 ). Unfavorable responses can also be predicted, especially when the presence of other types of immune cells (e.g.…”
Section: Composition Of the Tmementioning
confidence: 99%
“…They bind to Programmed death-1 (PD-1) expressed on activated CAR-T cells, inhibiting their function. Recent study also showed that the TME of large B cell lymphoma is the key determinant of CD19-CAR-T cell activity ( 41 ). Several strategies have been proposed to overcome the immunosuppressive effects of the TME, including the blockade of immune checkpoints, promoting CAR-T cell activity and remodeling the TME ( Figure 1 ).…”
Section: Approaches To Mitigate the Immunosuppressive Tumor Microenvi...mentioning
confidence: 99%